The ultra mentality - Foundations for maximising athletic mental performance - Gardner, A. J.; Gilbert, R. (Journal of Science and Medicine in Sport Plus, 2024)
For over 100 years there has been an academic pursuit of understanding and applying the principals of sport psychology to improve athletic performance. How is it that certain athletes do their best when it means the most while others "choke"? Meeting and exceeding the challenges that are presented can completely change the trajectory of any athlete's career. What is it that separates the good from the great and the great from the superstars? Is it motivation, preparation, determination, discipline, commitment, natural talent, physical strength, or work ethic? Maybe it is a combination of all of these characteristics. Without the right mentality everything can fall apart. In Alcoholics Anonymous, it is said, "you don't have a drinking problem - you have a thinking problem." The evidence is quite clear that the mental game can have a substantial impact, both for the better and for the worse, on performance. In this perspectives and viewpoints, we share our own insights from our experience for athletes to obtain the ultra-mentality and maximise their athletic performance. We have attempted to take simple words to briefly explain complicated concepts.